Analisis Strategi Pemilihan Vendor dalam Rangka Pengadaan Mobil Truk dengan Metode AHP pada PT Iron Bird Logistics - Sri Handoko Sakti; Junaidi Hendro; Muhammad Natser (Yayasan Putra Adi Dharma, 2026)
This study aims to determine the best truck vendor for PT Iron Bird Logistics by applying the Analytical Hierarchy Process (AHP) method. The research focuses on developing a strategic framework that integrates various qualitative and quantitative criteria into the vendor selection process. The methodology employs a case study approach, collecting primary data through questionnaires and in-depth interviews with relevant experts and managers within the company. The AHP method was applied by constructing a criteria hierarchy consisting of Quality, Cost, After-Sales Service, and Technology. The data were analyzed using Expert Choice software to calculate criteria weights and evaluate the seven pre-selected vendors. The analysis results show that the Quality criterion has the highest weight (0.425), followed by Cost (0.285), After-Sales Service (0.185), and Technology (0.105). Of the seven vendors evaluated, Vendor D achieved the highest score (0.218) and was determined to be the best vendor. The consistency ratio (CR) test yielded a value of 0.03 (< 0.1), indicating a consistent assessment. The value of this research lies in its practical contribution to the application of the AHP method for truck vendor selection, particularly in Indonesian logistics companies. The resulting framework offers a systematic and comprehensive approach that can be adopted by similar companies for strategic decision-making in fleet procurement.